Organic aerosols in a Brazilian agro-industrial area: Speciation and impact of biomass burning - Urban, R. C.; Alves, C. A.; Allen, A. G.; Cardoso, A. A.; Campos, M. L.A.M. (Elsevier, 2016)
This work presents the first comprehensive organic characterization of atmospheric aerosols from an agro-industrial region (São Paulo State, Brazil) highly impacted by biomass burning. The organic speciation was performed using different solvents of increasing polarity, enabling the identification and quantification of 172 different organic species by GC-MS. The mass of organic compounds reached 123μgm-3 in an aerosol sample collected during the sugar cane harvest period compared with 0.82μgm-3 in the non-harvest period. The samples most impacted by biomass burning were those with the highest percentages of non-polar compounds (n-alkanes; up to 96%). However, in absolute terms, the total mass of polar compounds in such samples was greater than for samples less impacted by this activity. Retene (a marker for biomass combustion) was the most abundant of the 19 polycyclic aromatic hydrocarbons quantified, corresponding to 14%-84%. This work shows that biomass burning was responsible for a benzo(a)pyrene equivalent index value that exceeded the recommendation of the World Health Organization. Principal component analysis indicated that agricultural biomass burning and emissions from crop processing facilities explained 42% of the variance of the data, while 37% was explained by urban emissions, 10% by vehicle emissions, and 10% by biogenic sources. This study provides insights into the emissions of a suite of organic compounds that could participate in anthropic alteration of regional cloud formation and precipitation patterns.
Keywords: Chemical speciation; Organic aerosol; PAH; Statistical analysis; Sugar cane